Fibrocyte localisation to the ASM bundle in asthma: bidirectional effects on cell phenotype and behaviour. Issue 11 (13th November 2020) - Saunders, Ruth; Kaur, Davinder; Desai, Dhananjay; Berair, Rachid; Chachi, Latifa; Thompson, Richard D; Siddiqui, Salman H; Brightling, Christopher E
Abstract: Objectives: Airway hyper‐responsiveness and persistent airflow obstruction contribute to asthma pathogenesis and symptoms, due in part to airway smooth muscle (ASM) hypercontractility and increased ASM mass. Fibrocytes have been shown to localise to the ASM in asthma however it is not known whether fibrocytes localise to the ASM in nonasthmatic eosinophilic bronchitis (NAEB) and chronic obstructive pulmonary disease (COPD). In addition, the potential consequences of fibrocyte localisation to ASM as regards asthma pathophysiology has not been widely studied. Methods: Fibrocytes and proliferating cells were enumerated in ASM in bronchial tissue using immunohistochemistry. The effects of primary ASM and fibrocytes upon each other in terms of phenotype and behaviour following co‐culture were investigated by assessing cell number, size, apoptotic status, phenotype and contractility in in vitro cell‐based assays. Results: Increased fibrocyte number in the ASM was observed in asthma versus NAEB, but not NAEB and COPD versus controls, and confirmed in asthma versus controls. ASM proliferation was not detectably different in asthmatics versus healthy controls in vivo . No difference in proliferation, apoptotic status or size of ASM was seen following culture with/without fibrocytes. Following co‐culture with ASM from asthmatics versus nonasthmatics, fibrocyte smooth muscle marker expression and collagen gel contraction were greater. Following co‐culture, fibrocyte CD14 expression was restored with the potential to contribute to asthma pathogenesis via monocyte‐mediated processes dependent on the inflammatory milieu. Conclusion: Further understanding of mechanisms of fibrocyte recruitment to and/or differentiation within the ASM may identify novel therapeutic targets to modulate ASM dysfunction in asthma. Abstract : Fibrocyte recruitment to the airway smooth muscle (ASM) is a feature of asthma but not chronic obstructive pulmonary disease or nonasthmatic eosinophilic bronchitis. Our in vitro data show that culture with ASM from asthmatics maintains a muscle‐like phenotype in fibrocytes and augments contractility. In addition, fibrocytes may retain the ability to participate in monocyte‐mediated processes, dependent on the composition of the local inflammatory milieu. Further understanding of mechanisms of fibrocyte recruitment to and/or differentiation within the ASM may identify novel therapeutic targets to modulate ASM dysfunction in asthma.